2007
DOI: 10.1503/cmaj.060875
|View full text |Cite
|
Sign up to set email alerts
|

Auricular acupuncture for pain relief after ambulatory knee surgery: a randomized trial

Abstract: A lmost 70% of operative procedures in North America are currently performed in an ambulatory setting.1 Despite advances in surgical techniques and modern methods of analgesia, 45% of patients suffer pain at home after ambulatory surgery, 2 and moderate to severe pain intensity at home is reported by 30% of ambulatory patients.3 Inadequate relief of pain after ambulatory surgery increases morbidity and health care costs and reduces patients' quality of life.4,5 To improve postoperative pain relief, an integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 28 publications
2
65
1
2
Order By: Relevance
“…Abbate 9 summarized 15 modalities used in AA, such as needles, pellets (Semen vaccariae ear seeds), magnetic pearls, electricity, et cetera. Current studies show that AA helps relieve a large number of diseases and complaints (i.e., anxiety, 10 postoperative pain, 11,12 chronic low-back pain, 13 and problems related to spinal-cord injuries 14 ).…”
Section: Introduction Imentioning
confidence: 99%
“…Abbate 9 summarized 15 modalities used in AA, such as needles, pellets (Semen vaccariae ear seeds), magnetic pearls, electricity, et cetera. Current studies show that AA helps relieve a large number of diseases and complaints (i.e., anxiety, 10 postoperative pain, 11,12 chronic low-back pain, 13 and problems related to spinal-cord injuries 14 ).…”
Section: Introduction Imentioning
confidence: 99%
“…In another study, the stimulation of the sympathetic AA point significantly decreased the stimulus-evoked electrodermal response compared with an AA stimulation to a non-specific point of the helix.. This resembles the design of studies performed by (Usichenko et al, 2005(Usichenko et al, , 2007where stimulation of the points in the central regions of the auricle was better than sham acupuncture at the non-specific points of the helix for reduction of postoperative analgesic requirement. Early studies of Auricular acupuncture have demonstrated beneficial effects on both pain and anxiety including pain associated with cancer, knee arthroscopy, and hip fracture and hip arthroplasty.…”
Section: Application and Effect Of Auricular Acupoint Pressing For Anmentioning
confidence: 60%
“…These involved therapeutic modalities including acupuncture injection, 38,39 electroacupuncture, 40,41 transcutaneous electro acupoint stimulation, 42,43 auricular acupuncture, 44,45 Korean hand acupressure, 46,47 and capsicum plaster used on acupuncture points. 48,49 These studies were excluded as they did not meet the selection criteria.…”
Section: Selection Of Papersmentioning
confidence: 99%